EFL STUDENTS’ PEDAGOGY FOR SOCIAL CONSTRUCTIVISM IN SPEAKING BLENDED MODE ACTIVITIES: A CASE STUDY - Dhea Setiawan (Journal of English Education Program (JEEP), 2022)
This article reports on a learning method using social constructivism on blended learning efl pedagogy in speaking class. This research investigated the activeness of twelfth grade students from six science classes, in learning English speaking applying both face to face and online classes. A case study research design was used in the present study, and the observation and interview data were collected transcribed, coded, and analyzed with triangulation, The findings revealed that learning using social constructivism is very important in students’ activities. So that students must be better in their preparation, and comprehend the teaching materials before attending the class for their readliness, activeness, and fully participation in classroom activities, It can be said that social constructivism is beneficially needed for students for equipping themselves to follow learning process both face to face and online learning. The present study calls for other researchers to do other issues in the same fied for responding the research gap: How a teacher can motivate students who are not ready in the teaching and learning process to be active in speaking in class despite their lack of understanding in learning, and how much time should be used for the teaching and learning process with the social constructivism method so that students can really master class learning in the classroom. appeal to teachers who only act as facilitators.